Rainfall Pattern: Gamma Distribution Method - Saharudin, Muhammad Syahmi; Zamri, Mohamad Syazani; Mohd Zaidi, Muhammad Najemi; Sahat, Suhaila (Multidisciplinary Applied Research and Innovation, 2022)
Our research is about rainfall pattern in Peninsular Malaysia from 2003 until 2018. Malaysia is popular with their irregular rainfall pattern for every year that can leads to unpredictable floods. The objective of our research is to determine the annual rainfall pattern and its characteristics in Kota Tinggi, Johor using Gamma in 2003-2018. For this study, we use gamma method in order to calculate the gamma distribution value of each year using the annual rainfall value. For the calculations, we use two software in order to finish this project which is Statistical Package for Social Science or also known as SPSS software and Microsoft Excel. In order to make sure this research will succeed, we need to calculate the gamma distribution in order to determine the maximum probability distribution of the annual rainfall. Gamma distribution can be calculated by using its formula to obtain the final value. In order to make sure the calculation is correct, we must double check the value of every aspect in the gamma equation such as shape and scale parameter that we found is correct. Based on our findings, we got all of the gamma value on every year from 2003 until 2018. Based on the annual rainfall graph and the gamma value, we know that Kota Tinggi, Johor receive a relatively frequent rain on the 2017 which receive 2618mm and has 2.01704×1070 gamma value along the year. Based on the calculation the characteristics of the rainfall is it has a moderate intensity that makes it raining for all year around. For the future studies, we can suggest that to use multiple gamma equation to make sure the result is more eligible.